Differential regulation of the eicosanoid biosynthesis pathway in response to Enterocytozoon hepatopenaei infection in Litopenaeus vannamei - Wananit Wimuttisuk; Pisut Yotbuntueng; Pacharawan Deenarn; Punsa Tobwor; Kamonluk Kittiwongpukdee; Surasak Jiemsup; Rapeepun Vanichviriyakit; Chanadda Kasamechotchung; Suganya Yongkiettrakul; Natthinee Munkongwongsiri; Siriwan Khidprasert; Vanicha Vichai (PLoS ONE, 2025)
The microsporidian Enterocytozoon hepatopenaei (EHP) is a highly contagious pathogen that causes severe growth retardation in penaeid shrimp. EHP infection damages the hepatopancreatic tubules, causes hematopoietic infiltration, and recruits granulocytes and inflammatory cells to the shrimp stomach and intestine. In this study, we investigated whether EHP infection induced the eicosanoid biosynthesis pathway in the gastrointestinal tract of the Pacific white shrimp Litopenaeus vannamei . Shrimp hepatopancreases, stomachs, and intestines were collected on days 0, 7, and 21 of the EHP cohabitation experiment for analysis. On day 7, the levels of cyclooxygenase (COX) and prostaglandin F synthase (PGFS) enzymes, which catalyze the production of prostaglandins, were elevated in the hepatopancreas of EHP-infected shrimp. The stomach of EHP-infected shrimp also contained higher levels of 12-hydroxyeicosatetraenoic acid (12-HETE) and 12-hydroxyeicosapentaenoic acid (12-HEPE) than the control shrimp. Nevertheless, the most significant impact of EHP infection on day 7 was observed in shrimp intestines, in which the levels of prostaglandin F 2α (PGF 2α ), 8-HETE, and four isomers of HEPEs were higher in the EHP-infected shrimp than in the control shrimp. As the EHP infection progressed to day 21, the upregulation of COX and PGFS persisted in the EHP-infected hepatopancreas, leading to increasing levels of PGF 2α and 15-deoxy-Δ 12,14 -prostaglandin J 2 (15d-PGJ 2 ). The upregulation of prostaglandins was in contrast with the decreasing levels of HETEs and HEPEs in the hepatopancreas of EHP-infected shrimp. Meanwhile, the stomach of EHP-infected shrimp contained higher levels of prostaglandin D 2 , PGF 2α , 15d-PGJ 2 , and most of the hydroxy fatty acids than the control shrimp. The levels of eicosanoid precursors, namely arachidonic acid and eicosapentaenoic acid, were upregulated in the shrimp gastrointestinal tract collected on days 7 and 21, suggesting that substrate availability contributes to the increasing levels of eicosanoids after EHP infection. Our study provides the first comprehensive analysis of the eicosanoid biosynthesis pathway in response to EHP infection. Moreover, the results indicate that eicosanoids are part of the host-pathogen interactions in crustaceans.